The Immediate Effect of a Textured Insole in Nonparetic Lower Limb Symmetry of Weight Bearing and Gait Parameters in Patients with Chronic Stroke - Mehdi Hassan Abadi; Behnam Hajiaghaee; Hasan Saeedi; Naser Amini (University of Social Welfare and Rehabilitation Sciences, 2016)
Objective Weight-bearing asymmetry is one of the main causes of balance disturbances in patients with hemiparesis and could cause standing problems and gait abnormalities for them. The purpose of this study was to investigate the immediate effects of wearing unilateral textured insoles on the symmetry of weight bearing during standing and gait parameters of patients with chronic stroke. Materials & Methods In this quasi-experimental study, 16 patients with hemiparesis were selected by simple non-probability sampling method. These patients had an average age(SD) of 52.12(6.94) years and their average(SD) post-injury duration was 33.12(16.4) months. Symmetry index during standing position (by using 2 equal weighting scales), step length symmetry, step length, and walking velocity (by using NeuroCom Balance Master Device) was measured in 3 conditions: without insole (barefoot), wearing textured insole with shore A-80 hardness, and textured insole with shore A-60 hardness. Results In this study, we conducted the multivariate analysis of variance for comparing 3 test conditions and Bonferroni test for paired comparing. The symmetry of step length showed a significant difference between no insole condition and using insole with A-80 hardness (P=0.004), as well as using A-80 hardness insole with A-60 hardness insole (P=0.011). However, there was no significant difference between using no insole and using insole with A-60 hardness (P=0.325). The results of symmetry index likened the step length results. This means that there was a significant difference between not using insole and wearing insole with A-80 hardness (P=0.022), also between the results of wearing 2 different insoles (P=0.019). However, no significant difference was observed between using no insole and using insole with A-60 hardness in spite of improvement in step length (P=0.325). Velocity of walking and step length was not meaningfully improved in any of the conditions. Conclusion The current study showed that obligatory use of affected limb side could improve symmetry of weight bearing in walking and standing position of patients with chronic stroke by overcoming the phenomenon of learned lack of using and correcting the failure of sending sensory signals to centers of movement controls. The results of this study showed that unilateral use of textured insole with shore A-80 in the unaffected side could immediately improve weight bearing symmetry and step length symmetry in patients with hemiparesis, but it has no effect on their walking speed and step length. Using insole with A-60 hardness did not significantly change any variables of tests. Considering the results of this study, these insoles can be used in balance exercises and walking of hemiparetic patients.